Receipt of other routinely recommended vaccines relative to receipt of seasonal influenza vaccines: Trends from medicare administrative data, 2013–2015. Issue 30 (16th July 2018) - Shen, Angela K.; Warnock, Rob; Chu, Steve; Kelman, Jeffrey A.
Abstract: Annual influenza vaccination campaigns emphasize the importance of getting vaccinated against influenza. These campaigns offer potential opportunities to raise awareness of all vaccines. We explored the peak timing of the receipt of influenza and other routinely recommended vaccinations. We examined administrative claims data of 31 million Medicare fee-for-service beneficiaries, eligible to receive vaccinations administered from 2013 to 2015 from Medicare Part B (medical insurance) and Medicare Part D (prescription drug benefit). From 2013 to 2015, 88% of over 50 million influenza vaccination claims occurred in September, October, and November. Claims for pneumococcal (42%), herpes zoster (36%), and tetanus-containing (32%) vaccines were also concentrated during these months. For pneumococcal vaccines, this concentration occurred across various provider settings, including traditional doctor's offices, pharmacies, and hospitals. Herpes zoster (92%) and tetanus-containing (72%) vaccines were largely administered in the pharmacy. Annual influenza vaccination efforts offer additional opportunities to assess, recommend, and administer other recommended vaccinations.